Urban Reforms and the Birth of City Planning in Rio de Janeiro and Recife (1904-1945) - Outtes, Dr. Joes (Diálogos Latinoamericanos, 2005)
This paper discusses urban reforms and the birth of city planning in Rio de Janeiro and Recife between the years 1904 and 1945. It deals with financial changes, political struggles, housing crises and the birth of city planning itself. The paper concludes that these urban reforms brought another image of the city, a new townscape and a different experience of living. These developments were characterised by proto-modern architecture, skyscrapers built on large avenues, distant housing with long journeys to work for the poorest, or overcrowded favelas (slum setlements) around the city centre.